Profil Hamba Tuhan Sejati & Hubungannya Dengan Efektivitas Para Pelayan Tuhan di GSJPDI ‘Adityawarman’ Surabaya - Widi Prasetyo; Daniel Ari Wibowo (Jurnal Teologi dan Pelayanan Kerusso, 2020)
The organization is a complex unit that seeks to allocate resources fully for the achievement of objectives. Both the resources relating to facilities and infrastructure as well as human resources. If an organization is able to achieve its stated goals, it can be said that the organization is effective. One of the goals of the organization is to achieve employee effectiveness and efficiency. Every organization needs to pay attention to the issue of work effectiveness where work effectiveness is the ability of employees to carry out work to bring the results that have been determined previously. For the Director, effectiveness is the key to organizational success. Effectiveness is not just doing the job right but how to focus resources and efforts for it. Efficiency is the use of minimum resources to achieve optimum results. Efficiency assumes that the correct goals have been determined and tries to find the best ways to achieve these goals. Efficiency can only be evaluated by relative judgments, comparing input and output received. An organization, both government and private organizations formed to achieve goals, needs factors that can be in the form of human resources, materials and tools to support activities. Of these three factors, human factors are the most dominant factors. In the effort to achieve organizational goals, humans are very important factors. Because humans are the main actors of the organization, it needs special attention compared to others. As the most important factor, people with the ability to carry out their duties will influence the success or failure of the organization in achieving its objectives. Abstrak Indonesia Setiap organisasi perlu memperhatikan masalah efektivitas kerja di mana efektifitas kerja merupakan kemampuan dari para karyawan dalam melaksanakan pekerjaan untuk mendatangkan hasil yang telah ditetapkan sebelumnya. Bagi Direktur, efektifitas adalah kuncikeberhasilan organisasi. Efektifitas tidak hanya melakukan pekerjaan dengan benar tetapi bagaimana melakukan memusatkan sumber daya dan upaya untuk itu. Efisiensi adalah penggunaan sumber daya secara minimum guna pencapaian hasil yang optimum. Efesiensi menganggap bahwa tujuan-tujuan yang benar telah ditentukan dan berusaha untuk mencari cara-cara yang paling baik untuk mencapai tujuan-tujuan tersebut. Efisiensi hanya dapat dievaluasi dengan penilaian-penilaian relatif, membandingkan antara masukan dan keluaran yang diterima. Suatu organisasi baik organisasi pemerintah maupun swasta yang dibentukuntuk mencapai tujuan, perlu faktor-faktor yang dapat berupa sumber daya manusia, material dan alat-alat penunjang kegiatan. Dari ketiga faktor tersebut, faktor manusia merupakan faktor yang paling dominan.Dalam usaha mencapai tujuan organisasi, manusia merupakan faktor yang sangat penting. Karena manusia menjadi pelaku utama organisasi maka perlu mendapat perhatian khusus dibanding yang lainnya. Sebagai faktor yangpaling penting, manusia dengan kemampuan yang dimiliki dalam menjalankantugasnya akan mempengaruhi berhasil tidaknya organisasi dalam mencapai tujuan.